First Letters After Exile by Thomas Mann, Hannah Arendt, Ernst Bloch, and Others. - Garz, Detlef; Kettler, David; Garz, Detlef (Anthem Press, 2021)
The book contains a number of studies focused on the post-war correspondence between noted exiles from Hitler's Germany and colleagues and friends who remained in Germany. These materials provide unique insights into the reshaping of relations among the correspondents, which figure decisively in decisions of exiles on questions of return.